2005
DOI: 10.1021/cm051949t
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystalline Submicrotubes from Small Organic Molecules

Abstract: The single crystalline submicrotubes of a small organic functional molecule, 2,4,5-triphenylimidazole (TPI), were successfully prepared with a facile method. A series of characterizations indicated that the tubes were obtained from the rolling followed by seaming of a preorganized two-dimensional sheet-like structure, whose formation was due to the efficient cooperation of several molecular recognition elements. The length and diameter of the TPI tubes can be readily controlled by adjusting the experimental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 35 publications
1
80
1
Order By: Relevance
“…[14] Small organic molecules (for example, 2,4,5-triphenylimidazole) have been used as a soft template to prepare single crystalline submicrotubes by using non-covalent intermolecular interactions, such as hydrogen bonding, p-p interactions, van der Waals contacts, and charge transfer interactions. [15] Inorganic and organic-inorganic nanofibrous materials have also been prepared by using soft templates. [16] Previous studies have demonstrated that different types of mercapto carboxylic acids, such as TGA, can be used to synthesize nanowires because these acids form complicated complexes with Cd 2þ ions.…”
mentioning
confidence: 99%
“…[14] Small organic molecules (for example, 2,4,5-triphenylimidazole) have been used as a soft template to prepare single crystalline submicrotubes by using non-covalent intermolecular interactions, such as hydrogen bonding, p-p interactions, van der Waals contacts, and charge transfer interactions. [15] Inorganic and organic-inorganic nanofibrous materials have also been prepared by using soft templates. [16] Previous studies have demonstrated that different types of mercapto carboxylic acids, such as TGA, can be used to synthesize nanowires because these acids form complicated complexes with Cd 2þ ions.…”
mentioning
confidence: 99%
“…[119] Recently, Yao and co-workers reported the fabrication of single-crystalline nano-and sub-micrometer tubes by inducing the self-assembly of the small organic functional molecules 2,4,5-triphenylimidazole (TPI) in water at different temperatures. [120] Typical scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images and the selected area electron diffraction (SAED) pattern of TPI tubes are shown in Figure 3. It can be seen that the TPI tubes have comparatively high monodispersity and open-ended structures.…”
Section: Self-assembly In the Liquid Phasementioning
confidence: 99%
“…In this light, 2,4,5-triphenylimidazole (TPI) was used to build 1D tubular host microstructures through a facile reprecipitation method due to its strong hydrogen bonds along the c crystal axis. [ 23 ] Figure 1 A illustrates that the self-assembly process of TPI tubes follows three stages: (i) nucleation, (ii) 1D growth, and (iii) termination. [ 24 ] At the beginning of self-assembly, TPI molecules quickly concentrate and nucleate into some short rod-like hollow structures ( Figure S1, Supporting Information).…”
Section: Doi: 101002/adma201104326mentioning
confidence: 99%